HUBUNGAN ANTARA KEPERCAYAAN DIRI DAN DUKUNGAN ORANG TUA DENGAN MOTIVASI BERWIRAUSAHA PADA SISWA SMK - Maulida, Siti Rochmah; Dhania, Dhini Rama (Jurnal Psikologi, 2012)
The aim of this study is to empirically examine the relationship between self-confidence and parental support with entrepreneurship motivation in vocational students. Subjects were 119 students of class XI in SMK Wisudha Karya Kudus. The sampling technique was cluster random sampling and the instruments were entrepreneurship motivation scale, self-confidence scale and parental support scale. Data were analysed using regression analysis between three variables with R= 0.481 (p <0.01). It means that there was a significant relationship between self-esteem and parental support with entrepreneurship motivation in vocational students. The main hypothesis proposed was thus received in this study. Self confidence and parental support predicting the entrepreneurship motivation at 23.1%. The correlation coefficient between the self-confidence and entrepreneurship motivation was 0.438 (p <0.01). It means that there was a significant positive relationship between self-confidence and entrepreneurship motivation in vocational students. The correlation coefficient between the variables of parental support and entrepreneurship motivation was r= 0.449 (p <0.01). It showed a significant positive relationship between parental support and entrepreneurship motivation in vocational students.Keywords: Entrepreneurship Motivation, Self Confidence, Parental Support